2019
DOI: 10.1002/jimd.12065
|View full text |Cite
|
Sign up to set email alerts
|

The neurological and psychological phenotype of adult patients with early‐treated phenylketonuria: A systematic review

Abstract: Newborn screening for phenylketonuria (PKU) and early introduction of dietary therapy has been remarkably successful in preventing the severe neurological features of PKU, including mental retardation and epilepsy. However, concerns remain that long‐term outcome is still suboptimal, particularly in adult patients who are no longer on strict phenylalanine‐restricted diets. With our systematic literature review we aimed to describe the neurological phenotype of adults with early‐treated phenylketonuria (ETPKU). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 96 publications
9
43
0
Order By: Relevance
“…Additionally, a notably impaired executive function in ETPKU patients has been well documented [11]. A recent review summarizes neuropsychological findings in ETPKU patients [12]. In response to these findings, recent guidelines recommend life-long Phe-restricted diet and new treatment targets for ETPKU patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a notably impaired executive function in ETPKU patients has been well documented [11]. A recent review summarizes neuropsychological findings in ETPKU patients [12]. In response to these findings, recent guidelines recommend life-long Phe-restricted diet and new treatment targets for ETPKU patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…The second limitation was related to the self-rating instruments, which could be influenced by some bias, such as memory bias, patient education, the complex psychological phenotype of adult PKU patients, and more practical issues, such as the availability of web-based material [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in many PKU patients with normal cognitive function Phe levels still influence brain performance ( 18 ). Alternatively, it has been shown that inconsistencies in neurocognitive, psychosocial and metabolic consequences of PKU remain, despite treatment ( 19 22 ).…”
Section: The Gut Microbiome In the Context Of Pkumentioning
confidence: 99%